Simultaneous-Equations Tests of the Natural Rate and Other Classical Hypotheses - Cuddington, John T. (Journal of Political Economy, 1980)
This paper tests the fundamental implication of classical stochastic macroeconomic models à la Sargent-Lucas, namely, that conditional means of real variables are invariant with respect to monetary and fiscal policy. Using a multiple-equations technique to examine U.S. data from 1952:II to 1972:III, the classical hypothesis (which includes the natural-rate hypothesis) is rejected. While such evidence does not completely rule out the possibility of classical behavior by the economy, it provides some reassurance for those predisposed toward policy activism.